Spectrophotometric Determination of Nickel(II) with 2,4-Dihydroxy-5-Bromopropiophenone Thiosemicarbazone - Gandhi, H.C.; DESAI, K.K. (Asian Journal of Chemistry, 2010)
2,4-Dihydroxy-5-bromopropiophenone thiosemicarbazone (DHBPT) was synthesized and used as a spectrophotometric reagent for nickel. Ni(II) forms yellow coloured complex between pH range 7.0 to 10.0 and shows maximum absorption at 375 nm. Molar absorptivity for Ni(II)-DHBPT is 2.586 x 103 L/mole cm. Ni(II) DHBPT has 1 : 2 (M : L) stoichiometry. Beer's law is obeyed up to 16.49 ppm for Ni(II). The reagent has been found to give satisfactory results for the analysis of nickel in german-silver alloy. Formation of the complex has been supported from the IR spectral data.